Effects of Chewing Different Flavored Gums on Salivary Flow Rate and pH - Maryam Karami Nogourani; Mohsen Janghorbani; Raha Kowsari Isfahan; Mozhgan Hosseini Beheshti (International Journal of Dentistry)
Chewing gum increases salivary flow rate (SFR) and pH, but differences in preferences of gum flavor may influence SFR and pH. The aim of this paper was to assess the effect of five different flavors of sucrose-free chewing gum on the salivary flow rate and pH in healthy dental students in Isfahan, Iran. Fifteen (7 men and 8 women) healthy dental student volunteers collected unstimulated saliva and then chewed one of five flavored gums for 6 min. The whole saliva was collected and assessed for 6 consecutive days. After unstimulated saliva was collected, stimulated saliva was collected at interval of 0-1, 1–3, and 3–6 minutes after the start of different flavored chewing gums. The SFR and salivary pH were measured. The SFR increased in all five flavored gums at 1, 3, and 6 minutes after start of chewing gums (𝑃<0.001). The flow rate of all products reached peak in the 1st minute of stimulation, except spearmint-flavored gums which reached peak in the 6th minute. In the 1st minute, the strawberry-flavored gums showed the highest SFR. During 1–3 minutes, strawberry- and apple-flavored gums showed higher SFR, respectively. Only the spearmint- and cinnamon-flavored gum significantly increased salivary pH. Gum flavored can affect the SFR and pH and special flavors can be advised for different individuals according to their oral conditions.